Cover Image, Volume 53, Issue 1. (27th January 2020) - Wu, Hao; Song, Yue; Li, Junqin; Lei, Xing; Zhang, Shuaishuai; Gao, Yi; Cheng, Pengzhen; Liu, Bin; Miao, Sheng; Bi, Long; Yang, Liu; Pei, Guoxian
Abstract : The cover image is based on the Original Article Blockade of adrenergic β‐receptor activation through local delivery of propranolol from a 3D collagen/polyvinyl alcohol/hydroxyapatite scaffold promotes bone repair in vivo by Hao Wu et al., https://doi.org/10.1111/cpr.12725 .